Arabic Language Methods and their Effects on the Scholars’ Differences in Understanding the Qur’an and Hadith Texts - Shah, Faisal Ahmad (Al-Bayān, 2016)
This article explains the importance of the Arabic language and its methods to understand the texts of the Qur’an and hadith. Arabic language scholars have set methods that should be followed in order to produce an accurate understanding of Qur’an and hadith texts. The mastery of the rules of the Arabic language is very important because any negligence will lead to deviation from the true meaning of the Qur’an and hadith. Through a direct analysis of the works of selected scholars, this article discusses scholars’ differences of understanding towards Qur’an and hadith texts according to their Arabic language proficiency.